Testing Job Matching Services for Unemployed Educated Youth in Jordan - Groh, Matthew; McKenzie, David; Shammout, Nour; Vishwanath, Tara (World Bank, Washington, DC, 2014)
This note tests the extent to which search and matching frictions are the cause of high levels of unemployment for educated youth in Jordan, and whether a job matching service can reduce unemployment.